Arbovirus Prevalence in Mosquitoes, Kenya - LaBeaud, A. Desiree; Sutherland, Laura J.; Muiruri, Samuel; Muchiri, Eric M.; Gray, Laurie R.; Zimmerman, Peter A.; Hise, Amy G.; King, Charles H. (Emerging Infectious Disease journal, 2011)
Few studies have investigated the many mosquito species that harbor arboviruses in Kenya. During the 2006–2007 Rift Valley fever outbreak in North Eastern Province, Kenya, exophilic mosquitoes were collected from homesteads within 2 affected areas: Gumarey (rural) and Sogan-Godud (urban). Mosquitoes (n = 920) were pooled by trap location and tested for Rift Valley fever virus and West Nile virus. The most common mosquitoes trapped belonged to the genus Culex (75%). Of 105 mosquito pools tested, 22% were positive for Rift Valley fever virus, 18% were positive for West Nile virus, and 3% were positive for both. Estimated mosquito minimum infection rates did not differ between locations. Our data demonstrate the local abundance of mosquitoes that could propagate arboviral infections in Kenya and the high prevalence of vector arbovirus positivity during a Rift Valley fever outbreak.
Keywords: Arboviruses; zoonoses; viruses; Rift Valley fever virus; West Nile virus; vectors; mosquitoes; RT-PCR; Kenya; research